Pengaruh Training And Development Terhadap Employee Comptence Lembaga Pemasyarakatan Narkotika Kelas IIA Yogyakarta - Annisa Primaharani; Padmono Wibowo (Jurnal Riset dan Inovasi Manajemen, 2023)
This research aims to evaluate the impact of training and development on the level of employee competence at Class IIA Narcotics Penitentiary in Yogyakarta. The enhancement of employee competence in this penitentiary is facilitated through training programs covering various technical fields. Each employee has the right to participate in and receive structured training. Data was collected using a questionnaire, and data analysis was conducted through simple linear regression analysis. The research results indicate that Training and Development have a significant impact on employee competence. The research employed a quantitative approach with random sampling techniques. The research subjects consisted of 30 employees from Class IIA Narcotics Penitentiary in Yogyakarta. Data processing was carried out using the statistical analysis tool IBM SPSS 25, which involved entering and calculating the respondents' assessments of the research instrument distributed.